Motivation matters : a workbook for school change - Ginsberg, Margery B., 1954- (Jossey-Bass, 2004)
Provides concrete approaches to facilitate school renewal based on principles of intrinsic motivation--among students and educators. It describes strategies that award-winning high-poverty public schools have used to become not only more inclusive but more relevant and challenging to students of diverse student groups. In these schools academic achievement has increased; disproportional rates of achievement among diverse student groups is being reduced; and incidents of school violence have sharply declined.